The Interaction of Ocimum basilicum, Perilla frutescens and Mentha spicata Essential Oils With Norfloxacin Against Antibiotic‐Resistant Salmonella Spp. That Cause Disease in Chickens - Nguyen Van Vui; Nguyen Thuy Linh; Nguyen Thi Kim Quyen; Kim Nang; Le Thi Tuyet Trinh (Veterinary Medicine and Science)
ABSTRACT Background The misuse of antibiotics in livestock farming has led to the emergence of antibiotic‐resistant bacteria, which pose a serious threat to global animal and human health. Essential oils extracted from the leaves of Ocimum basilicum, Perilla frutescens and Mentha spicata contain bioactive compounds with bactericidal properties. Objectives This study aimed to evaluate the bactericidal activity of Ocimum basilicum, Perilla frutescens and Mentha spicata essential oils and their combination with the antibiotic norfloxacin, against antibiotic‐resistant Salmonella spp. isolated from diseased chickens. Methods The antibiotic susceptibility testing of the isolated bacteria was conducted using the disc diffusion method. The bactericidal efficacy of essential oils and antibiotics was assessed by determining the minimum bactericidal concentration. The interaction between essential oils and antibiotics was analysed using the fractional bactericidal concentration index through the microdilution chequerboardtechnique. Results Salmonella typhimurium and Salmonella enteritidis were recovered from the organs of infected chickens. Isolated Salmonella spp. displayed significant resistance to amoxicillin, ampicillin, streptomycin and cefuroxime. The essential oils of Ocimum basilicum and Mentha spicata demonstrated similar minimum bactericidal concentration (MBC) values of 8,000 µg/mL, while the essential oil of Perilla frutescens showed a higher MBC value of 10,000 µg/mL. Analysis of the interaction between these essential oils and norfloxacin indicated that both Ocimum basilicum and Mentha spicata exhibited a synergistic effect, whereas Perilla frutescens exhibited an additive effect when combined with norfloxacin in eradicating Salmonella spp. Conclusion The study concluded that combining essential oils from three herbs with the antibiotic norfloxacin was highly effective in fighting antibiotic‐resistant Salmonella spp. isolated from infected chickens.